2017
DOI: 10.1016/j.pharep.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide and sorafenib as programmed cell death inducers of human glioma cells

Abstract: Sorafenib and Temozolomide applied in combination are potent apoptosis inducers in T98G and MOGGCCM cells. ER stress precedes the elimination. Blocking of Hsp expression has a greater impact on ER stress rather than apoptosis induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…Glioma is an aggressive brain tumor that exhibits high resistance to chemotherapy [20]. The functional effects of lncRNAs have been verified, including their role as key regulators of translational and transcriptional products that influence cellular functions [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Glioma is an aggressive brain tumor that exhibits high resistance to chemotherapy [20]. The functional effects of lncRNAs have been verified, including their role as key regulators of translational and transcriptional products that influence cellular functions [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…However, phase I, II and III clinical trials have demonstrated a modest efficacy with this antiangiogenic drug, alone or in combination (Gerstner et al, ; Nabors et al, ). Instead, sorafenib has been used in combination with temozolomide as programmed cell‐death inducers of human glioma cells (Jakubowicz‐Gil et al, ). Sorafenib (Sb) is a multiple kinase inhibitor (from BRAF, VEGFR, PDGFR pathways) that targets both tumor‐cell proliferation and angiogenesis.…”
Section: Therapeutic Approaches Focused On Ecm and Invasionmentioning
confidence: 99%
“…However, phase I, II and III clinical trials have demonstrated a modest efficacy with this antiangiogenic drug, alone or in combination (Gerstner et al, 2015;Nabors et al, 2015). Instead, sorafenib has been used in combination with temozolomide as programmed cell-death inducers of human glioma cells (Jakubowicz-Gil et al, 2017).…”
Section: Th Er a P Eu Ti C A Pp R Oa Ch Es F Ocu S E D On Ec M An Dmentioning
confidence: 99%
“…Thus, prolonged 17 TMZ treatment is a relevant option either as up-front or as adjuvant treatment. 18 Clinical trials have shown a similar efficacy of TMZ vs RT for 1p/19q-codeleted 19 tumors [11,12]. Also, RT is associated with late neurocognitive toxicity.…”
Section: Introductionmentioning
confidence: 98%
“…The second one was lethally damaged tumor cells because of the action of 58 the therapy D(t). Temozolomide effect on proliferative cells is a complex one, leading 59 to death through different 'programmes' [18][19][20]. We put together the different 60 processes into two groups, each described by a term in our equations.…”
mentioning
confidence: 99%